2015
DOI: 10.1007/s10853-015-9115-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and electrical conductivity in Al–Si/Cu/Fe/Mg binary and ternary Al alloys

Abstract: This study investigated 30Al-Si, Al-Cu, AlFe, Al-Mg, Al-10Si-Cu, Al-10Si-Fe, and Al-10Si-Mg binary and ternary Al alloys, which are among the most commonly used commercial alloys. The thermal and electrical conductivity of the gravity castings of these alloys were measured. The results indicated that when 1 wt% Si, Cu, or Fe was mixed with commercial Al with 99.8 % purity, the thermal conductivity decreased from 213.5 Wm −1 K −1 to approximately 190-210 Wm −1 K −1 . The thermal conductivity remained at a nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…According to Figure 7, it is worth noting that the conductivity performance of different states for Al-2Fe-xCo alloys are in the following sequence: as-cast < annealing < rolling. It is known that many factors affect the thermal conductivity of alloys, such as alloy composition [2,7,36,37], heat treatment [10,11,38,39], melt treatment [40,41], plastic deformation [1,42], and so on. In our study, compared with the as-cast samples, the thermal conductivities of alloys significantly increase after annealing From Figure 7a, the thermal diffusivity of as-cast specimens first increases from 0.837 cm 2 /s for the Al-2Fe alloy to 0.856 cm 2 /s for Al-2Fe-0.3Co alloy by improving the amplitude of 2.3%, and then gradually decreases with increasing Co content.…”
Section: Conductivity Performance Of Al-2fe-xco Ternary Alloysmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Figure 7, it is worth noting that the conductivity performance of different states for Al-2Fe-xCo alloys are in the following sequence: as-cast < annealing < rolling. It is known that many factors affect the thermal conductivity of alloys, such as alloy composition [2,7,36,37], heat treatment [10,11,38,39], melt treatment [40,41], plastic deformation [1,42], and so on. In our study, compared with the as-cast samples, the thermal conductivities of alloys significantly increase after annealing From Figure 7a, the thermal diffusivity of as-cast specimens first increases from 0.837 cm 2 /s for the Al-2Fe alloy to 0.856 cm 2 /s for Al-2Fe-0.3Co alloy by improving the amplitude of 2.3%, and then gradually decreases with increasing Co content.…”
Section: Conductivity Performance Of Al-2fe-xco Ternary Alloysmentioning
confidence: 99%
“…Aluminum alloys possessing higher thermal conductivity always exhibit poor mechanical properties and vice versa. The properties of aluminum alloys are controlled by certain factors, such as the alloying element [ 2 , 7 ], preparation process [ 8 , 9 , 10 ], heat treatment [ 10 , 11 ], etc. Moreover, the specific thermal resistivity (thermal resistivity increment of the alloy derived from unit mass addition) of the alloying elements for Al alloys varies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although solid solubility has a great influence on the thermal conductivity of alloys, Lumley et al [7] treated die cast alloys by using a T7 temper and reported that the thermal diffusivity and thermal conductivity of the alloy increased. Chen et al [8] suggested that precipitation and heat treatment could influence the thermal conductivity of aluminum alloys by experimentally and computationally investigating binary and ternary Al alloys. Thus, many researchers have attempted to enhance the thermal properties of aluminum alloys by various heat treatments.…”
Section: Introductionmentioning
confidence: 99%